2020
DOI: 10.1007/s40124-020-00216-7
|View full text |Cite|
|
Sign up to set email alerts
|

The ICU Liberation Bundle and Strategies for Implementation in Pediatrics

Abstract: Purpose of Review We briefly review post-intensive care syndrome (PICS) and the morbidities associated with critical illness that led to the intensive care unit (ICU) liberation movement. We review each element of the ICU liberation bundle, including pediatric support data, as well as tips and strategies for implementation in a pediatric ICU (PICU) setting. Recent Findings Numerous studies have found children have cognitive, physical, and psychiatric deficits after a PICU stay. The effects of the full ICU libe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 89 publications
0
22
0
4
Order By: Relevance
“…As mortality in the PICU has decreased, several quality improvement initiatives have been aimed at mitigating the long-term psychologic, social, and physical impairment of critical illness (43). ICU liberation bundles, also known as ABCDEF Bundles (44) (Table 3), are evidence-based guidelines to liberate patients from the harmful effects of a PICU stay (10,43). It should be noted that sedation protocols are a critical element of these bundles, directly addressing "A" and "C" and having an impact on "B", "D", and "E".…”
Section: Role Of Sedation Protocols Within Picu Liberation Bundlesmentioning
confidence: 99%
“…As mortality in the PICU has decreased, several quality improvement initiatives have been aimed at mitigating the long-term psychologic, social, and physical impairment of critical illness (43). ICU liberation bundles, also known as ABCDEF Bundles (44) (Table 3), are evidence-based guidelines to liberate patients from the harmful effects of a PICU stay (10,43). It should be noted that sedation protocols are a critical element of these bundles, directly addressing "A" and "C" and having an impact on "B", "D", and "E".…”
Section: Role Of Sedation Protocols Within Picu Liberation Bundlesmentioning
confidence: 99%
“…Previous studies reported that benzodiazepines are independent risk factors for delirium [ 16 , 17 ]; therefore, the replacement of benzodiazepines in favour for alternative drugs like alpha-2 agonists has been advocated [ 18 ]. The recently published clinical practice guidelines for the management of Pain, Agitation, Neuromuscular Blockade, and Delirium in critically ill pediatric patients with consideration of the PICU Environment and Early Mobility (PANDEM) and the Recommendations for analgesia and sedation in critically ill children admitted to intensive care unit [ 8 , 19 ] both recommend the use of alpha 2 -agonists over benzodiazepines as a first-line sedative.…”
Section: Discussionmentioning
confidence: 99%
“…As surviving critical illness can have long-term effects on both PICU survivors and parents, who play a key role in helping to recover, follow-up care for parents is necessary to be able to adequately support the patient and parents. Early mobility exercises, the practice of physical therapy during critical illness, and family engagement/empowerment are promising intervention strategies ( 91 , 92 ).…”
Section: Discussionmentioning
confidence: 99%